Pengaruh Aktivitas Olahraga Jalan Kaki terhadap Tingkat Stres pada Pekerja PHK Akibat Corona Virus Disease 2019 - I Gede Widjanegara; Ayu Dyah Kusuma Dewi Widiarsa; I Nengah Sumirta (Jurnal Gema Keperawatan, 2021)
Stress is a self-response to various problems and problems that each individual cannot overcome and will cause mental disorders. One way to overcome stress symptoms is by doing walking sports activity therapy. The purpose of this study was to determine the effect of walking exercise therapy on the stress level of workers who experienced layoffs due to Covid-19 in Jembrana District in 2021. The design of this study used a pre-experimental design with a one-group pre-post test design approach. The sampling method is non probability sampling using purposive sampling method. The number of samples is 22 people. Hypothesis testing used statistical Wilcoxon Sign Rank Test with a p value = 0.000 (α = 0.05). The research instrument used the Depression Anxiety Stress Scale 42 (DASS 42). The results showed that there was a significant effect (p = 0.000) of walking sports activity therapy on the stress level of layoff workers in Jembrana District in 2021 and show that the walking sports activity therapy reduced the stress level of workers who had laid off. Thus, workers who have been laid off should increase their physical activity on foot to stimulate the production of endorphins.